Karakteristik Penderita Demam Tifoid Rawat Inap Anak Di Rsud Abdul Wahab Sjahranie Samarinda - Rachman, Yudhistira Nugraha, Dr. Mochammad Wildan, Sp.A (2017)
Background: Typhoid fever is a disease caused by Salmonella typhi which is affected by environmental factors and human interaction towards it. The disease is contagious and can affect many people that can cause an outbreak. Children are a group with the most risk of typhoid fever, especially children at school age in which children interacts more with the environment. Typhoid fever in children provide clinical picture which varies from mild to life-threatening complications, where it is difficult for doctors to diagnose. Objective: To determine the characteristics of children, typhoid fever patients hospitalized in Abdul Wahab Sjahranie hospital, Samarinda. Method: This study used a descriptive, cross-sectional research design with secondary data in the form of medical records. Samples in this research are amounted to 158 medical records of children with typhoid fever. Data were analyzed using the computer program of Statistical package for the Social Science (SPSS) version 23.0 for Windows. Result: The highest proportion is in the group of school age (62.0%), male gender (57.6%) and patients originated from Samarinda (74.7%). Most clinical symptoms were fever (100%), the largest clinical sign is tongue typhoid (10.1%), and the highest laboratory results are lymphocytosis (50.0%). The average length of hospitalization in children with typhoid fever was 4.68 (5 days) with a coefficient of variation 63.9%. The proportion of patients with typhoid fever with relative lymphocytosis was 17 (10.75%). Conclusion: There were no significant differences between the clinical characteristics of children with typhoid fever with the group of school and pre-school aged.